2023
DOI: 10.1093/nar/gkad472
|View full text |Cite
|
Sign up to set email alerts
|

DDMut: predicting effects of mutations on protein stability using deep learning

Abstract: Understanding the effects of mutations on protein stability is crucial for variant interpretation and prioritisation, protein engineering, and biotechnology. Despite significant efforts, community assessments of predictive tools have highlighted ongoing limitations, including computational time, low predictive power, and biased predictions towards destabilising mutations. To fill this gap, we developed DDMut, a fast and accurate siamese network to predict changes in Gibbs Free Energy upon single and multiple p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Due to high-quality data is valuable for the robustness of the model, the previous test set has been incorporated into the training set to enhance the generalization ability of the model in recent methods . This makes it difficult to compare the different methods fairly.…”
Section: Resultsmentioning
confidence: 99%
“…Due to high-quality data is valuable for the robustness of the model, the previous test set has been incorporated into the training set to enhance the generalization ability of the model in recent methods . This makes it difficult to compare the different methods fairly.…”
Section: Resultsmentioning
confidence: 99%
“…Strain correlates with ∆∆G almost as well as tailored ∆∆G predictors.-To put the strain-stability correlations in context, we compare them with two state-of-the-art ∆∆G predictors, DDMut and FoldX (see Methods). 14,15 FoldX predicts ∆G from structure using empirical energy-based potentials; it is used to calculate ∆∆G by first a generating structure for the mutant based on a reference WT structure, which enables calculation of ∆G for both WT and mutant structures. DDMut uses a neural network to predict ∆∆G, using a reference structure and a mutation as input.…”
Section: Resultsmentioning
confidence: 99%
“…∆∆G predictors-We use two state-of-the-art methods to predict ∆∆G: FoldX 5, 21 and DDMut. 14 We use the API for the DDMut web server to predict ∆∆G. For FoldX, we use the BuildModel command to generate structures of the WT and mutant sequences and ∆∆G predictions.…”
Section: Methodsmentioning
confidence: 99%
“…To gain insights into unannotated variant impact, focusing on the LDLR class B repeats, we used the full wild-type LDLR structure from the AlphaFold Protein Structure Database 76,77 and the MODELLER 78 -generated mutant structures to calculate changes in interatomic interactions using Arpeggio 79 . Additionally, we predicted the effects of variants on protein stability (ΔΔ𝐺, negative value indicates destabilization) with DDMut 80 ( Supplementary Table 8 ). We found that the 26 significant LDLR class B variants induce more destabilizing effects, disrupt more hydrophobic interactions, have lower relative solvent accessibility 81 (0.041 of maximum residue solvent accessibility), and have higher wild-type residue depth as compared to the other observed variants in this region (Fig.…”
Section: Resultsmentioning
confidence: 99%